A PPP-type pseudophosphatase is required for the maintenance of basal complex integrity in Plasmodium falciparum - Alexander A. Morano; Rachel M. Rudlaff; Jeffrey D. Dvorin (Nature Communications, 2023)
Abstract During its asexual blood stage, P. falciparum replicates via schizogony, wherein dozens of daughter cells are formed within a single parent. The basal complex, a contractile ring that separates daughter cells, is critical for schizogony. In this study, we identify a Plasmodium basal complex protein essential for basal complex maintenance. Using multiple microscopy techniques, we demonstrate that PfPPP8 is required for uniform basal complex expansion and maintenance of its integrity. We characterize PfPPP8 as the founding member of a novel family of pseudophosphatases with homologs in other Apicomplexan parasites. By co-immunoprecipitation, we identify two additional new basal complex proteins. We characterize the unique temporal localizations of these new basal complex proteins (late-arriving) and of PfPPP8 (early-departing). In this work, we identify a novel basal complex protein, determine its specific role in segmentation, identify a new pseudophosphatase family, and establish that the P. falciparum basal complex is a dynamic structure.